Cladocera (Crustacea: Ctenopoda, Anomopoda) from southern Mexico, Belize and northern Guatemala, with some biogeographical notes - Elías-Gutiérrez, Manuel; Kotov, Alexey A.; Garfias-Espejo, Tania (Zootaxa, 2006)
Different surveys in the Campechano–Petenense biogeographical province, including a part of Yucatan Peninsula, Belize, and North of Guatemala (Departments of Peten and Alta Verapaz), produced a list of 56 species of the Cladocera. Studied water bodies included small temporary pools, sinkholes (named cenotes), permanent lagoons, wetlands, and Peten Lake. We increase the number of known cladoceran species from Mexico by adding eight new records, and provide the first published species list for Belize, as well as for the Mayan Mountains and intermittent rivers from Guatemala. Interesting taxa found are Diaphanosoma bergamini Paggi & da Rocha, 1999; Macrothrix spinosa King, 1853; M. elegans Sars, 1901; Grimaldina brazzai Richard, 1892; Picripleuroxus quasidenticulatus Smirnov, 1996; Ephemeroporus tridentatus (Bergamin, 1939); Graptoleberis sp.; Alona cf. ossiani Sinev, 1998; Oxyurella ciliata Bergamin, 1939, and O. longicaudis (Birge, 1910). The majority of these species are Neotropical representatives, and the Mexican records are the northernmost. Few other taxa, such as the recently described Leydigia louisi mexicana Kotov, Elías-Gutiérrez & Nieto, 2003, are related to African species or widely distributed, like Ilyocryptus spinifer Herrick, 1882. Some species, as E. tridentatus (Bergamin) and O. ciliata Bergamin were rare in the samples.